Classical HDACs in the regulation of neuroinflammation. (November 2021) - Dai, Yunjian; Wei, Taofeng; Shen, Zexu; Bei, Yun; Lin, Haoran; Dai, Haibin
Abstract: Neuroinflammation is a key factor of the pathology of various neurological diseases (brain injury, depression, neurodegenerative diseases). It is a complex and orderly process that relies on various types of glial cells and peripheral immune cells. Inhibition of neuroinflammation can reduce the severity of neurological diseases. The initiation, progression, and termination of inflammation require gene activation, epigenetic modification, transcriptional translation, and post-translational regulation, all of which are tightly regulated by different enzymes. Epigenetics refers to the regulation of epigenetic gene expression by epigenetic changes (DNA methylation, histone modification, and non-coding RNAs such as miRNA) that are not dependent on changes in gene sequence and are heritable. Histone deacetylases (HDACs) are a group of important enzymes that regulate epigenetics. They can remove the acetyl group on the lysine ϵ-amino group of the target protein, thereby affecting gene transcription or altering protein activity. HDACs are involved in the regulation of immunity and inflammation. HDAC inhibitor (HDACi) has also become a new hotspot in the research of anti-inflammatory drugs. Therefore, the aim of the current review is to discuss and summarize the role and mechanism of different HDACs in neuroinflammation and the corresponding role of HDACi in neurological diseases, and to providing new ideas for future research on neuroinflammation-related diseases and drug development. Highlight: HDACs are involved in the regulation of neuroinflammation. The review provides evidence of the role of HDAC in the therapy of neuroinflammation-related diseases. This review suggests the potential use of HDAC inhibitors in neurological diseases.